Assessing the inhalation pathogenicity of the mycoinsecticide Beauveria bassiana LF14 in mice - Cazorla Perfetti, Dalmiro (2015)
Biosafety tests were conducted on albino mice (NMRI strain) to evaluate pathogenic effects of a native isolate LF14 of B. bassiana, highly virulent to Rhodnius prolixus and Triatoma maculata (Triatominae), vectors of Chagas disease in Venezuela. A total of 1x109 conidias/ml of the fungus was administered to the animals by nasal drops. Body weight control and clinical and behavioural evaluations were done daily. Likewise, clearance of fungus was estimated by direct examination and culturing of intranasal samples, and infectivity by performing mycological and histopathological test after necropsies at 3, 7 and 14 days post-inoculation. Animals no showed discernible pathological changes or death and all had active-normal behaviour. Body weight increased in both treated and control mice groups, with statistically difference between sexes (p<0.0000). Anatomopathological changes were not detected. Only was observed viable but nongerminated conidia at day 3 in lung and traquea tissues, suggesting no evidence of fungal multiplication. The results allowed suggesting the innocuity of B. bassiana LF14 when was administered intranasal to Mus musculus (NMRI strain).